Spatial distribution of trace elements and potential contamination sources for surface sediments of the North-Western Black Sea, Romania - Bucşe, Andra; Pârvulescu, Oana Cristina; Vasiliu, Dan; Rădulescu, Florina; Lupaşcu, Naliana; Ispas, Bogdan Adrian (Frontiers in Marine Science, 2024)
It is essential to determine the concentrations of metals/metalloids in marine sediments and their contamination status to develop appropriate pollution control strategies and/or improve existing ones. Spatial distribution of aluminum (Al) and some trace elements, i.e., arsenic (As), chromium (Cr), copper (Cu), mercury (Hg), nickel (Ni), lead (Pb), and zinc (Zn), accumulated in surface sediments of the north-western (NW) Black Sea (Romanian zone) was evaluated. Sediment samples were collected in 2019 from 32 stations located at water depths in the range of 12.7–149 m. The mean values ± standard deviations (SD) of element concentrations were as follows: 3.9 ± 1.6% for Al, 11.2 ± 10.2 mg/kg for As, 64.8 ± 27.0 mg/kg for Cr, 32.7 ± 15.0 mg/kg for Cu, 0.10 ± 0.09 mg/kg for Hg, 45.3 ± 23.8 mg/kg for Ni, 24.6 ± 9.6 mg/kg for Pb, and 68.0 ± 28.0 mg/kg for Zn. These values are not significantly different (p > 0.05) from those found in a previous study on surface sediments collected in 2018 from 22 stations located in the same area, but at lower water depths (13.5–67 m). Contamination factor (CF) was used to assess the contamination status of surface sediments. The mean values of CF (0.26–1.23) reveal low to moderate contamination with Pb and low contamination with the other elements. Principal component analysis (PCA) and correlation analysis indicated that As, Cu, Ni, Hg, Pb, and Zn were associated with clay, silt, and organic matter, suggesting that these elements mainly came from the Danube discharges and also from local anthropogenic sources, whereas Al, Cr, and partly Hg, Pb, and Zn originated from rock/soil weathering and erosion. The concentration levels of As, Cu, Hg, Ni, Pb, Zn, TOC, silt, and clay were higher in sediments collected from stations generally located at higher water depths (up to 118 m), suggesting that the TEs associated with the finer carriers were transported offshore by currents and waves, whereas the concentration levels of Al, Cr, Hg, and Zn were higher in sediments with lower levels of CaCO3 content (10.1–24.3%), collected from shallower stations (water depths of 12.7–42.0 m).